The black book - Pamuk, Orhan, 1952-; Freely, Maureen, 1952- (London : Faber and Faber, 2006)
Galip is a lawyer living in Istanbul. His wife, the detective-novel-loving Rüya, has disappeared. Could she have left him for her ex-husband, Celâl, a popular newspaper columnist? But Celâl, too, seems to have vanished. As Galip investigates, he finds himself assuming the enviable Celâl's identity, wearing his clothes, answering his phone calls, even writing his columns. Galip pursues every conceivable clue, but the nature of the mystery keeps changing, and when he receives a death threat, he begins to fear the worst. With its cascade of beguiling stories about Istanbul, The Black Book is a brilliantly unconventional mystery, and a provocative meditation on identity. For Turkish literary readers it is the cherished cult novel in which Orhan Pamuk found his original voice, but it has largely been neglected by English-language readers. Now, in Maureen Freely's beautiful new translation, they, too, may encounter all its riches.--Publisher description.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Missing persons -- Fiction; False personation -- Fiction; Istanbul (Turkey) -- Fiction; Legal stories; Mystery fiction; Fiction